Modification of thermoregulatory response to heat stress by body fluid regulation - Akira Takamata (Japanese Society of Physical Fitness and Sports Medicine, 2012)
The thermoregulatory system interacts vitally with the body fluid regulatory system. Thermoregulatory response during heat stress, such as sweating and cutaneous vasodilation, stimulates body fluid regulatory response by elevating plasma osmolality and reducing central blood volume. Isotonic hypovolemia, or baroreceptor unloading, and plasma hyperosmolality, in turn, inhibit thermoregulatory response to heat stress, suggesting that body fluid regulation is given priority over thermoregulation. On the other hand, osmoregulatory vasopressin secretion and thirst are augmented by elevated body core temperature. Heat acclimation enhances thermoregulatory response to heat stress. Adaptation of the body fluid regulatory system, such as increased plasma volume and reduced osmotic inhibition of thermoregulatory response, is possibly involved in the mechanism for the enhancement of thermoregulatory response to heat stress by heat acclimation. In this review, we discuss the interaction between body fluid regulation, especially osmoregulation, and thermoregulation mainly in humans.